Does the social distancing measures impact collaboration in software processes? - Chaves, Victor Manaia G.; Machado, Sofia M. B.; Outão, Juliana Carvalho S. do; Santos, Rodrigo Pereira dos; Diirr, Bruna (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2022)
Context: Social distancing measures to reduce the impacts of the COVID-19 pandemic bring challenges for several organizations and their Information Systems (IS). Problem: Social distancing were suddenly implemented, with no adequate planning. Furthermore, there is not a clear understanding of the impacts of social distancing measures on the software development teams’ work. Solution: This study aims to identify the presence and impacts of social distancing on collaboration between people, as well as on activities and technologies used in software development, from the perspective of professionals who work in software development teams. IS Theory: The research was developed under the aegis of the Team Resilience Theory. Method: A field study was conducted based on structured interviews and qualitative analysis. Results: In general, it was observed no impact on the software processes activities, although their performance was affected. It was also observed that the impact on the collaboration dynamics in software development was perceived in different ways, by several team members. This study identified the most common tools used by organizations, as well as the benefits and challenges of collaboration in software development after social distancing measures. Contribution: The impacts of social distancing on collaboration in software development were identified, reinforcing the Team Resilience Theory and similar study conducted in the beginning of the COVID-19 pandemic. This study contributes to the Grand Research Challenge ”Systemic and Socially Aware Perspective for Information Systems”.